Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/242
|View full text |Cite
|
Sign up to set email alerts
|

Relevance in Structured Argumentation

Abstract: We study properties related to relevance in non-monotonic consequence relations obtained by systems of structured argumentation. Relevance desiderata concern the robustness of a consequence relation under the addition of irrelevant information. For an account of what (ir)relevance amounts to we use syntactic and semantic considerations. Syntactic criteria have been proposed in the domain of relevance logic and were recently used in argumentation theory under the names of non-interference and crashresistance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Their motivation, however, has been questioned by [10]. 14 In Definition 5 we follow what is the most frequent approach in the ASPIC-family, namely to assume that undercutting attacks are preference-independent. However, since our main results concern ASPIC-frameworks without undercut this choice is insignificant for this study.…”
Section: Attack and Defeatmentioning
confidence: 99%
See 1 more Smart Citation
“…Their motivation, however, has been questioned by [10]. 14 In Definition 5 we follow what is the most frequent approach in the ASPIC-family, namely to assume that undercutting attacks are preference-independent. However, since our main results concern ASPIC-frameworks without undercut this choice is insignificant for this study.…”
Section: Attack and Defeatmentioning
confidence: 99%
“…We use this term in order to indicate that the addition of "irrelevant" information leads to contaminating effects (see also[14]). "Irrelevance" is disambiguated differently in the two versions considered.…”
mentioning
confidence: 99%
“…For instance, in [54] such issues are considered and paraconsistent logics are taken to overcome trivialization, a weaker version of crash-resistance from [41]. Recently, in [37], properties of some well-known structured argumentation systems (including sequent-based argumentation) that warrant several relevance desiderata are investigated. 34 In [9] similar problems are discussed and resolved by introducing relevant attack rules.…”
Section: Example 19 Consider the Set Smentioning
confidence: 99%
“…By doing so, any completeness-based semantics can be used for the framework. Recently, in [37] a general framework is defined, in which several well-known structured argumentation frameworks can be represented. It is shown that for this general framework and under a few further assumptions, both crash-resistance and non-interference are obtained for many completeness-based semantics.…”
Section: Summary Related Work and Future Researchmentioning
confidence: 99%
“…For our study of enforcement of sets of formulas, we take a general approach to structured argumentation (Borg and Straßer 2018) so the results hold for many of the well-known approaches (Besnard et al 2014). We allow formulas to be added to the knowledge base, and show under which conditions on the attack relation and on the new information in the knowledge base a set of formulas can be enforced.…”
Section: Introductionmentioning
confidence: 99%